PCLN-04. BRAIN TUMOR PATIENT DERIVED ORTHOTOPIC XENOGRAFTS INDUCE TUMORS OF MOUSE ORIGIN. Issue 2 (22nd June 2018) - Strand, Andrew; Cole, Bonnie; Leary, Sarah; Olson, James
Abstract: Between 2009 to 2014 we established 50 patient derived orthotopic xenograft (PDOX) lines representing a wide spectrum of pediatric brain tumors. Eight lines repeatedly failed short tandem repeat identity testing and genomic methylation analysis. Tumors in these eight lines had a common histologic appearance distinct from the source tumors and suggestive of hematopoietic cells. These tumors showed leptomeningeal and ventricular dissemination and were very aggressive. Human-specific antibodies did not stain the tumors. RNAseq analysis confirmed these tumors to be purely mouse. RNAseq and cell surface marker analysis suggested an early myeloid cell of origin. In a rare case, co-existence of PDOX and mouse tumor was observed in a single animal. RNAseq also revealed high expression of murine leukemia virus (MuLV). All NOD immunodeficient mice contain functional endogenous MuLV retrovirus in their genome. We are testing a model where infiltrating immune cells in the primary tumor or the tumor cells themselves provide paracrine stimulation of mouse myeloid cells, which serve as targets for retroviral transformation. These studies may help us to understand novel mechanisms relevant for brain tumor–immune system interactions. As more labs develop and share these invaluable models, it is critical to utilize quality control steps to verify the lineage of PDOX lines. Removal of the endogenous MuLV by breeding or CRISPR technology to create a "clean" host mouse strain should be a priority for the translational research community.